The Legitimacy of the Patient Story: The Unofficial Autoethnography - Kathy Saldana (The Beryl Institute, 2024)
While communication is the foundation of patient experience, survey data and comments are the primary source of results. The focus on data, though meaningful, reduces humans to text on reports. With a focus of autoethnography in both her baccalaureate and post-graduate studies, the author, (a fulltime patient experience professional) shares her professional focus on the value of the data and comments, esteeming it all as valuable research given by the only people who can report patient experience - patients. She compares her stance regarding patient experience before and after receiving a diagnosis of breast cancer. The author shares how the experience as a patient with a life-threatening illness impacted her professional beliefs, including demonstrating purposeful, personal concern for patients, valuing patient experience data and comments, and encouraging others to do the same.